One Day the Emails Will End - Manley, Stewart (Wiley, 2018)
The emails usually arrive around once a week. Sometimes they come in spurts. Sometimes weeks pass without one. They say that the wild pigs have been uprooting the banana grove. The cold weather seems to have affected the chickens' ability to lay eggs. The moon is full. It has been raining for days. The old cow at the ranch house has finally died.